Nas ondas das ciências : uma experiência educativa na rádio comunitária primavera, PA - ALMEIDA, Jamilla de Nazaré de Oliveira (Universidade Federal do Pará, 2023)
Thisresearch aimsto look into the educational experience of the CommunityRadio of the Municipality of Primavera-Pará as a didactic-pedagogical tool for the dissemination of educational contents in Science, contributing to the integral formation of 4th and 5th year students during the Covid-19 pandemic. We approach the characteristics, themes and educational curriculum of the municipality as strategies and source of educational information on the contents of the referred discipline. Based on interviews with teachers, parents and students about radio and its role as a broadcaster of teaching and learning in this pandemic period, we sought to analyze the social context, marks, impacts and characteristics of this remote education. The main theoretical and methodological framework provides a brief review of the use of radio for education. We see the importance of radio for the Amazon, as well as for the Primavera community, even in a time of effervescence on the internet and social networks, with an emphasis on the relationship established between listeners and speaker teachers/students. The qualitative analysis also showed us that the school public is the one that most participates in the broadcasts, as well as the public of parents and teachers from other cities are also present, making us have new subsidies for the analysis of the current research context.